Pengurangan Penggunaan Plastik Sebagai Bahan Dasar Kemasan Produk Untuk Mengurangi Limbah Di Masyarakat - Benny Eligius Sinaga; Lusia Oktaviani Br Tamba; Tamim Hasyimi; Meilinda Suriani Harefa (Fakultas Teknik Universitas Cenderawasih, 2023)
Plastic is often used for various purposes in human life in very large quantities. From food packaging to automotive materials needs. Plastic is a very well-know material and is widely used as a material for making automotive components, besides metals, such as iron. The main problem with plastics is that they produce waste that doesn’t melt down naturally. It takes a very long time to produce all the plastic waste from the earth’s surface. Contolling the usse of plastic is becoming increasingly difficult, which will also cause air temperatures to be higher than usual, because the polymer has no [ores. Currently, actors must start reducing the use of plastic in their production. This is important to stop the high level of environmental pollution caused by plastic waste.